Developmental Relationships of Four Exhausted CD8+ T Cell Subsets Reveals Underlying Transcriptional and Epigenetic Landscape Control Mechanisms - Beltra, Jean-Christophe; Manne, Sasikanth; Abdel-Hakeem, Mohamed S.; Kurachi, Makoto; Giles, Josephine R.; Chen, Zeyu; Casella, Valentina; Ngiow, Shin Foong; Khan, Omar; Huang, Yinghui Jane; Yan, Patrick; Nzingha, Kito; et al. (Immunity (Cambridge, Mass.), 2020)
CD8+ T cell exhaustion is a major barrier to current anti-cancer immunotherapies. Despite this, the developmental biology of exhausted CD8+ T cells (Tex) remains poorly defined, restraining improvement of strategies aimed at “re-invigorating” Tex cells. Here, we defined a four-cell-stage developmental framework for Tex cells. Two TCF1+ progenitor subsets were identified, one tissue restricted and quiescent and one more blood accessible, that gradually lost TCF1 as it divided and converted to a third intermediate Tex subset. This intermediate subset re-engaged some effector biology and increased upon PD-L1 blockade but ultimately converted into a fourth, terminally exhausted subset. By using transcriptional and epigenetic analyses, we identified the control mechanisms underlying subset transitions and defined a key interplay between TCF1, T-bet, and Tox in the process. These data reveal a four-stage developmental hierarchy for Tex cells and define the molecular, transcriptional, and epigenetic mechanisms that could provide opportunities to improve cancer immunotherapy. [Display omitted] •Ly108 and CD69 define four Tex subsets linked in a hierarchical developmental pathway•Two TCF1+ subsets, effector-like and terminally exhausted subsets, are identified•Key transcriptional, epigenetic, and biological changes define subset transitions•TCF1, T-bet, and Tox coordinate Tex subset development and dynamics Beltra et al. define a hierarchical developmental pathway for CD8+ T cell exhaustion, revealing four stages and multistep transcriptional and epigenetic dynamics underlying subset transitions and subset-associated biological changes.